2019
DOI: 10.1002/ange.201901771
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alkali Metal in α‐MnO2 Catalyzed Ammonia‐Selective Catalysis

Abstract: The unexpected phenomenon and mechanism of the alkali metal involved NH 3 selective catalysis are reported. Incorporation of K + (4.22 wt %) in the tunnels of a-MnO 2 greatly improved its activity at lowt emperature (50-200 8 8C, 100 %c onversion of NO x vs.5 0.6 %c onversion over pristine a-MnO 2 at 150 8 8C). Experiment and theory demonstrated the atomic role of incorporated K + in a-MnO 2 .R esults showed that K + in the tunnels could form as table coordination with eight nearby O sp 3 atoms.The columbic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…On the basis of the results of this work and previous reports, the Eley–Rideal (E–R) and Langmuir–Hinshelwood (L–H) mechanisms coexist in the NH 3 -SCR reaction over (P/Ti-1/2)15@AC 45 , 50 , 51 . Both the gaseous and adsorbed NO reacted to the surface adsorbed NH 3 due to the carbon and titanium composite structure.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…On the basis of the results of this work and previous reports, the Eley–Rideal (E–R) and Langmuir–Hinshelwood (L–H) mechanisms coexist in the NH 3 -SCR reaction over (P/Ti-1/2)15@AC 45 , 50 , 51 . Both the gaseous and adsorbed NO reacted to the surface adsorbed NH 3 due to the carbon and titanium composite structure.…”
Section: Resultssupporting
confidence: 67%
“…In addition, the characterization peaks at 1460 and 875 cm −1 for both AC and (P/Ti-1/2)15@AC were intensified possibly because of the adsorbed NH 3 dehydrogenation process (Fig. 3 b, d), which was reported as the controlling step of denitrification 45 , 46 . On the basis of the XPS results, the additional surface oxygen of the sample after the SCR reaction increased by 4.66% and 0.94% of AC and (P/Ti-1/2)15@AC (Table 3 ).…”
Section: Resultsmentioning
confidence: 93%
“…In Table 1, after a long period leaching test, the content of K + remained a constant, which indicated that the K + incorporated in the tunnels of α-MnO2. The result is highly consistent with the conclusions of Ref [7]. K + ions in the tunnel would promote the adsorption and activation of NH3 has been proved.…”
Section: The Content Of Treated Emamsupporting
confidence: 92%
“…In addition, the potassium ion in the EMAM remained a certain content after many times water wash process. It also should be taken into account because alkali metals generally have a certain effect on the SCR process [7]. In order to take full advantage of EMAM to produce low temperature SCR catalyst, it is much meaningful to figure out the effect of Pb and K ion on the low temperature SCR in the EMAM.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, nanozymes usually have active centers or electron transport structures similar to natural enzymes by regulation strategy, which endow the nanozymes with efficient activity [1,15]. Surface acid-base active sites of metal oxides have been investigated in interfacial catalysis, such as heterogeneous industrial catalytic reactions, organic synthesis, and polymerization reaction [16][17][18]. The surface Lewis acid sites have an unoccupied orbital and the Lewis base can provide a lone pair of electrons [19].…”
Section: Introductionmentioning
confidence: 99%